On the Relationship between the Fractal Dimension of Geomagnetic Variations at Altay and the Space Weather Characteristics - Alexey Gvozdarev; Roman Parovik (Mathematics, 2023)
The fractal dimension of geomagnetic field component variations (horizontal—H, vertical—Z and magnetic declination—D) at the Baigazan magnetic station at Russian Altay, for the period 2011–2013, were calculated using the Higuchi method. The daily variation of Higuchi Fractal Dimension (HFD) for the D, H, Z components of the geomagnetic field were investigated, and its contribution to the variability of HFD was found to be from 30 to 40 percent of the total variance. A correlation analysis of the fractal dimension of the variations of the D, H, Z components with the Auroral Electrojet (AE) index and solar wind characteristics was carried out. Negative correlations with logarithms of the AE-index, interplanetary magnetic field (IMF) strength and solar wind velocity were found. About 25 percent of the HFD variance is controlled by the variability of these characteristics. Pair and partial correlation coefficients for these parameters were calculated for every month of 2011–2013.